Diseño de un sistema de bombeo para acueducto de Mambo, Atlántico (2018)
The project began with the identification of the problem, a diagnosis was made of the current situation of the collection process and existing filtering devices, then a conceptualization of the different collection systems, pumps, filters and pipes was carried out.